The Real Income Shares of Labor, Human and Physical Capital: Determination Method and First Results for Germany - Peter E.J. Steffen (Hamburg University, Department Socioeconomics, 2013)
A method is presented that allows to separate the total labor income into parts of basic labor and human capital using annual micro data. As results yearly total income shares of physical and human capital and labor are obtained for a single country. The method is applied to Germany using micro data of the years 1976, 1985, 1995, and 2006. The obtained average income shares are in agreement with the well known results of Mankiw, Romer and Weil [8] if only employed workers are considered. If self-employed labor is also taken into account, the share ratios of physical and human capital and labor change to sK : sH : sL = 0:18 : 0:26 : 0:55. This result differs considerably from the generally expected share ratios for developed countries of 1/3 : 1/3 : 1/3. Further on, the development of the German income shares are investigated. The observed variation is in contradiction to a constant behavior as expected from Kaldor's stylized facts. The source could be traced to considerable changes in the quali cation structure of the German work force.
Keywords: D33; E25; J24; 330; human capital; Mikrozensus; annual factor income shares; factor share development